Effects of Neem Leaf Volatiles on Submerged Cultures of Aflatoxigenic Aspergillus parasiticus - Zeringue, H. J. (1994)
Microbe-free compressed air was passed continuously for a 3-day test period through an enclosed system containing fresh neem leaves; the resultant emitted volatiles were passed over the surface of submerged liquid cultures of a wild-type aflatoxigenic isolate of Aspergillus parasiticus. Aflatoxin determinations for the fungal culture that received neem-derived volatiles, after a 3-day incubation period, resulted in a 90% overall reduction in aflatoxin production and a 51% reduction in fungal biomass when compared with cultures that did not receive neem volatiles. In a separate experiment but in a similarly enclosed system, volatiles from fresh neem leaves were collected on a small Tenax column and were thermally desorbed and cryogenically focused on a capillary gas chromatography column. The neem volatiles were subsequently separated and identified by gas chromatography-mass spectrometry. Sixty-eight compounds were identified by comparison of retention times and mass spectra with either authentic compounds or spectra from a computer-assisted library database of mass spectra. It was found that 10% of the total headspace volatiles were composed of C(3) to C(9) alkenals, which are toxic to aflatoxigenic Aspergillus spp., which could explain the bioactivity that resulted in reduced biomass in the neem-treated cultures.